Distress in Portuguese Family Members Bereaved by Suicide: An Exploratory Study - Santos, Sara (2015)
The present study examined the impact of several sociodemographic and suicide related variables on the distress of family members bereaved by suicide. A sample of Portuguese family members bereaved by suicide (N=93) living in the Alentejo region completed a sociodemographic and suicide information questionnaire and the Brief Symptom Inventory. Forward Multiple Linear Regression Analysis demonstrated that several sociodemographic and suicide variables related with general distress, depression and anxiety. Results contribute to characterize family members bereaved by suicide and have implications for the implementation of postvention programmes.